2020
DOI: 10.15342/ijms.7.192
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic Assessment of the Quality of Post & Core Restorations Performed by Dental Students at Qassim University Dental Clinics

Abstract: Introduction: A post usually made of prefabricated or custom made that is fitted into a prepared root canal of a natural tooth. Core is the foundation restoration which restores adequate coronal anatomy of a vital or endodontically treated tooth. When the post is combined with a core, it provides retention and resistance for an artificial crown. The primary purpose of the post is to retain a core restoration and crown, and also to redistribute the stresses onto the root, thereby diminishes the risk of coronal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 12 publications
4
10
3
Order By: Relevance
“…The present study revealed that posts were more frequently used in maxillary teeth. These results supported the findings by Jamani et al, Al-Hamad et al, Mathar and Almutairi, and Mattoo et al 22 , 24 , 26 , 27 Our findings showed that most of the teeth restored with posts were premolars, followed by anterior teeth then molars. Our results agree with findings reported by Mathar and Almutairi, where 57.2% of the cases were premolars.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The present study revealed that posts were more frequently used in maxillary teeth. These results supported the findings by Jamani et al, Al-Hamad et al, Mathar and Almutairi, and Mattoo et al 22 , 24 , 26 , 27 Our findings showed that most of the teeth restored with posts were premolars, followed by anterior teeth then molars. Our results agree with findings reported by Mathar and Almutairi, where 57.2% of the cases were premolars.…”
Section: Discussionsupporting
confidence: 93%
“… 22 , 26 , 27 However, this study showed lower values in terms of post length to root length (33%) in comparison to Mattoo et al (40.5%) 22 and Mathar and Almutairi (60.8%) but was superior to the results of Jamani et al and Nimigean et al (39.64% and 29.91%). 23 , 24 , 27 …”
Section: Discussioncontrasting
confidence: 82%
See 3 more Smart Citations